PERAN GURU DALAM MENGATASI PERILAKU INDISIPLINER SISWA DI KELAS VIII A SMP KEMALA BHAYANGKARI - Rizky Amaliny, Shelly (Tanjungpura University, 2018)
This research aims to find out teacher's role in overcoming students undiscipline behavior by directing, guiding, supervising, and leading in class VIII A of Kemala Bhayangkari Middle School. The research approach used was a qualitative approach with descriptive method. Data collection techniques that were used are observation, interviews, and documentation studies. The analysis in this study was presented in a qualitative descriptive manner using 8 informants, consisting of social study teacher, information technology communication's teacher, guidance counseling's teacher, and five students who behave undiscipline in class VIII A. The result of this research indicates that the teachers have played a role in overcoming the undisciplined behavior of students in class VIII A. The role of directing is when the teacher make students accustomed to dress well and pray before or after learning. A teacher also plays a role in guiding students through providing the guidance for students who behave an undisciplined behavior. Then, the teacher also plays a role in supervising which is when a teacher controls students and provides reprimands or sanctions for students who behave in undisciplined ways. The final role of the teacher is that the teacher has a role in leading which is the teacher is a good role model for students.